Sustainable use and conservation of biodiversity in the district Antioquia - Huarochiri - González Farroñay, Zoila Irene (2022)
The objective of this research is to determine the influence of sustainable use on the conservation of biodiversity in the district of Antioquía-Huarochirí, the research has included the community members who, through the NGO CIED in 2007, temporarily achieved economic development and social, thanks to the skills of the community members and credit support. Its development was achieved due to the planting of typical organic fruits of the place such as apples and quinces, however the community members asked that the NGO withdraw so that they can make their own decisions. This meant the neglect of the sustainable use of natural resources and the non-conservation of biodiversity. Today, the land is no longer productive as it was 14 years ago, the fruits do not have the same flavor, there is no relationship between sustainable use and the conservation of biodiversity, it is difficult for them to spend on organic inputs to produce fruits with the same characteristics. The research was carried out with a qualitative strategy of descriptive exploratory level. 5 community members were selected, of them, 3 were managers. Before applying the interview, they were informed of the visit to this community, the same one that did not materialize due to the COVID-19 pandemic, the data has been obtained through cell phone calls, therefore, that tourism was an alternative and is the activity that allows them to generate income for their families.